The assassination of Margaret Thatcher : stories - Mantel, Hilary, 1952- (Henry Holt and Company, 2014)
"From one of Britain's most accomplished, acclaimed, and garlanded writers, Hilary Mantel delivers a brilliant collection of contemporary short stories that demonstrate what modern England has becomeIn The Assassination of Margaret Thatcher, Hilary Mantel's trademark gifts of penetrating characterization, unsparing eye, and rascally intelligence are once again fully on display.Her classic wicked humor in each story--which range from a ghost story to a vampire story to near-memoir to mini-sagas of family and social fracture--brilliantly unsettles the reader in that unmistakably Mantel way. Mantel brutally and acutely writes about gender, marriage, class, family, and sex, cutting to the core of human experience. Unpredictable, diverse, and even shockingly unexpected, each story grabs you by the throat within a couple of sentences. The Assassination of Margaret Thatcher displays a magnificent writer at the peak of her powers. "--